KAJIAN AKTIVITAS ANTIMALARIA SENYAWA TURUNAN BISARIL KUINOLON DENGAN METODE HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS (HKSA) - , Mega Sari Juane Sofiana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Quantitative Structure-Activity Relationship (QSAR) analysis of bisaryl quinolone derivatives as antimalarial agents has been conducted using electronic and molecular descriptors. The descriptors were obtained from semi-empirical AM1 calculation. A multiple linear regression and artificial neural network (ANN) methods were used for QSAR models building on antimalarial activity and inhibition of PfNDH2 (Plasmodium falciparum type II NADH: quinone oxidoreductase) activity studies, respectively. The best equation of QSAR model on antimalarial activity study is pIC50= 2.064 â 0.003 (V) â 59.693 (qN1) â 11.338 (qC5) â 2.068 (qC6) + 2.036 (qC7) + 49.063 (qO11) with statistical parameters r2 = 0.751 and PRESS = 2.164. QSAR models of PfNDH2 inhibition study was resulted the best equation with polarizability and atomic net charges of N1 and C22 descriptors (r2 = 0.834). The best final equation was applied to design and predict more potent compounds as antimalarial agent. A new compound, 6,7-difluoro-2-(3-(4-(trifluoromethoxy) phenoxy)phenyl)quinoline-4(1H)-one with high antimalarial activity and inhibition of PfNDH2 activity has been proposed. The compound showed antimalarial activity against P. falciparum of 3.387 nM and inhibitory IC50 against PfNDH2 of 7.588 nM.